2014
DOI: 10.1007/s10096-014-2225-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an antimicrobial stewardship programme on the use of antimicrobials and the evolution of drug resistance

Abstract: Misuse of antibiotics can provoke increased bacterial resistance. There are no immediate prospects of any new broad-spectrum antibiotics, especially any with activity against enterobacteria, coming onto the market. Therefore, programmes should be implemented to optimise antimicrobial therapy. In a quasi-experimental study, the results for the pre-intervention year were compared with those for the 3 years following the application of an antimicrobial stewardship programme. We describe 862 interventions carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Eighteen of 22 studies measured relevant outcomes related to AMR [7, 10, 11, 17, 19, 21, 23, 33, 34, 43, 6365, 68, 82, 8890]. Of these studies, 11 (61%) found a statistically significant change in AMR following implementation of a hospital ASP.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen of 22 studies measured relevant outcomes related to AMR [7, 10, 11, 17, 19, 21, 23, 33, 34, 43, 6365, 68, 82, 8890]. Of these studies, 11 (61%) found a statistically significant change in AMR following implementation of a hospital ASP.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from hospital settings have shown that decreases in antibiotic resistance of gram negative bacteria do occur after the introduction of antimicrobial stewardship, [27][28][29] but the changes typically take years. 30 In NHs, we expect a similar slow rate of reduction in resistance, especially when considering other risk factors, such as hospital antimicrobial exposure, can rarely be concomitantly controlled. 31 Thus, the trends we observed are encouraging.…”
Section: Discussionmentioning
confidence: 98%
“…Since 2008, the HCS has employed a multidisciplinary programme for early intervention in patients with positive blood cultures (except the ICU and the paediatrics department), staffed by clinicians from the infectious disease and microbiology groups [6, 7]. Positive blood cultures are notified at an early stage by the microbiology service group, at a joint meeting with experts in the treatment of infectious diseases.…”
Section: Methodsmentioning
confidence: 99%